2023
DOI: 10.1021/acsami.2c18224
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lifespan Lithium Metal Batteries Enabled by a Hybrid Artificial Solid Electrolyte Interface Layer

Abstract: Lithium metal batteries based on metallic Li anodes have been recognized as competitive substitutes for current energy storage technologies due to their exceptional advantage in energy density. Nevertheless, their practical applications are greatly hindered by the safety concerns caused by lithium dendrites. Herein, we fabricate an artificial solid electrolyte interface (SEI) via a simple replacement reaction for the lithium anode (designated as LNA-Li) and demonstrate its effectiveness in suppressing the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The Ag-decorated Li anode was prepared by pretreating the Li foil with AgNO 3 (0.05 M) dissolved in DME-NMP (9:1) for 30 min. The Ag-decoration could greatly improve the lithium puncture resistance. , The PEO-LLZTO (EO/Li = 15, 10 wt %) separator was prepared by the casting method, whose thickness was 80 μm . To prevent the cathode active materials dissolving into PEO that induces the noxious “polysulfide shuttling” effect, a thin layer of Li 3 PS 4 was sprayed on the top of the Li 2 S cathode with the Li 3 PS 4 precursor sol and sintered together with the cathode.…”
Section: Methodsmentioning
confidence: 99%
“…The Ag-decorated Li anode was prepared by pretreating the Li foil with AgNO 3 (0.05 M) dissolved in DME-NMP (9:1) for 30 min. The Ag-decoration could greatly improve the lithium puncture resistance. , The PEO-LLZTO (EO/Li = 15, 10 wt %) separator was prepared by the casting method, whose thickness was 80 μm . To prevent the cathode active materials dissolving into PEO that induces the noxious “polysulfide shuttling” effect, a thin layer of Li 3 PS 4 was sprayed on the top of the Li 2 S cathode with the Li 3 PS 4 precursor sol and sintered together with the cathode.…”
Section: Methodsmentioning
confidence: 99%
“…3b); an ultralong lifespan of 6500 h was achieved in the symmetric cell test at a current density of 2 mA cm −2 and a capacity of 1 mAh cm −2 [64] . Similar hybrid ASEI layers, including sulfide/LiF [65] , Li 2 Se/LiCl [66] , Ag/LiF [67] , and Li 3 Sb/ LiF [68] , impressively improved the electrochemical performance of LMBs. Zhang et al realized that the flexibility of the ASEI layer should be considered and, therefore, adopted a flexible carbon nanotube (CNT) as the scaffold for the Li 3 N@c/s-CNT layer.…”
Section: Multicomponent Inorganic Layersmentioning
confidence: 99%
“…Several strategies have been developed to overcome these drawbacks, such as porous structure construction [9][10][11][12] , artificial solid-electrolyte-interface (SEI) layer formation [13][14][15][16] , and novel binder design [14,17,18] . Researchers also found that downsizing the Si particles to nanometers helps suppress particle pulverization, but the considerable surface area of nanosized Si leads to abundant side reactions, thus decreasing the Coulombic efficiency [19] .…”
Section: Introductionmentioning
confidence: 99%